Binding of arabinan or galactan during cellulose synthesis is extensive and reversible. (1st August 2015) - Lin, Dehui; Lopez-Sanchez, Patricia; Gidley, Michael J.
Highlights: Binding of pectic side chains studied during synthesis of bacterial cellulose. Arabinan and galactan each bind extensively (>200 mg/g cellulose). Bound polymers are not immobilized and cellulose crystallinity is not affected. Almost all bound galactan or arabinan is released under agitation. Implications for plant cell wall functional properties are discussed. Abstract: Arabinans and galactans are major components of the side-chains of pectin in plant cell walls. In order to understand how pectin side-chains interact with cellulose, in this work we studied the interaction of de-branched arabinan (from sugar beet) and linear galactan (from potato) during the synthesis of cellulose by Gluconacetobacter xylinus (ATCC 53524) to mimic in muro assembly. The binding studies reveal that arabinan and galactan are able to bind extensively (>200 mg/g of cellulose) during cellulose deposition, and more than pectin (from apple) in the absence of calcium. 13 C NMR revealed that associated arabinan, galactan or apple pectin molecules were neither rigid nor affected cellulose crystallinity, and there was no apparent change in cellulose architecture as reflected in scanning electron micrographs. De-binding of arabinan, galactan or apple pectin occurred as a result of washing, indicating a reversible binding to cellulose, which was modelled in terms of a surface-controlled process. Implications for structural models of primary plant cell walls and possible roles for cellulose binding of arabinan- and galactan-rich pectins in biological processes are discussed.